Supramolecular enzyme organization : quaternary structure and beyond - Friedrich, P. (Peter), 1936- (Pergamon Press ; Akademiai Kiado, 1984)
Supramolecular Enzyme Organization: Quaternary Structure and Beyond provides a comprehensive discussion of enzyme interactions. It attempts to place conceptually related phenomena in a common perspective by first scrutinizing enzyme interactions at the quaternary level and then moving on towards higher orders of organization.